Pengaruh Pelatihan, Motivasi dan Pengembangan Karier Terhadap Kinerja Guru TK di Kecamatan Jabung - Sinta Fathiyar Maulida; Achmad Agus Priyono; Satria Putra Utama (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of training, motivation and career development on the performance of kindergarten teachers in Jabung District. The type of research used is quantitative. The sample of this research was taken by simple random sampling technique or simple random sample by using the slovin formula, the number of samples was 98 respondents. The data analysis method used in this study is multiple linear regression analysis. Using (F test) for simultaneous hypothesis testing and (t test) for partial testing. The results of this study indicate that simultaneously training, motivation, and career development have a positive and significant effect on the performance of kindergarten teachers in Jabung District. While partially training has a positive and significant effect on the performance of kindergarten teachers in Jabung District, motivation partially has a positive and significant effect on the performance of kindergarten teachers in Jabung District, and career development partially has no significant positive effect on the performance of kindergarten teachers in Jabung District. Keywords: Training, Motivation, and Career Development